The impact of ownership structure on financial reporting quality in the east - Qaiser Rafique, Yasser; Abdullah, Al Mamun; Hook, Margurite (Emerald Group Publishing Ltd., 2017)
Purpose: This paper aims to focus mainly on the relationship between ownership structure and earnings management of a developed and two developing economies, and is distinct from prior research. Design/methodology/approach: Using a sample of firms from three countries (Australia, Malaysia and Pakistan), the detailed ownership evolutions for the period 2011-2013 were observed. Findings: Overall, the authors find that in the East, ownership concentration is negatively associated with financial reporting quality. Individual ownership and group ownership were negatively associated with earnings management in Pakistan, however, not in Malaysia where the same were positively associated. Further, the result of this study indicated that state ownership is negatively associated with firm performance. Among the control variables, it was found that larger firms were negatively correlated with financial reporting, while firms with a larger board size and mature in the maneuver were coupled positively with earnings management. Originality/value: The results highlight the highly individualized effects of blockholders and the need for research to further understand the mechanisms through which shareholders impact financial reporting quality. © 2017, © Emerald Publishing Limited.